HYDROELECTRIC ENERGY CAPACITY OF VAN LAKE - Tuna, M. Cihat (Yildiz Technical Univ, 2012)
Lake Van, which has a volume of 607 km(3), is the world's fourth, and Turkey's largest soda lake. Situated at 1,648 meters above mean sea level, the lake has a volcanic origin, created by huge lava flows from the Nemrut and Sipan volcanoes. Its surface area is 3,700 square kilometers with an average depth of 170 meters and a maximum depth of 457 meters. Water level of Lake Van increased about 2 meters for 1987-1996 periods. Such a rise caused destruction of some socio-economical activities in the lake vicinity. Lake Van and its surroundings were announced as the natural disaster area. Moreover, this rise caused prohibition for settlement under elevation of 1655 m, moreover the areas under elevation of 1652 m were announced as national private. Van Lake Basin is an efficiency basin in terms of hydropower generation possibility, due to its decrasing precipitation trend, important surface water potential and possibility of high head. In this study, as a clean, local and renewable energy source, potential of hydroelectric energy in Van Lake was examined in addition, to the hydropower center construction, feasibility and cost, installed capacity and amount of generated energy in the Van Lake Hydropower. Consequently, income and expense ratio (Profitability) were calculated as 3.51 for the Van Lake HEPP.
Keywords: Van Lake; hydroelectric; profitability